2020
DOI: 10.31235/osf.io/cpkj6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“My Husband Thinks I’m Crazy”: COVID-19-Related Conflict in Couples with Young Children

Abstract: Objective: We examine how disruptions related to the COVID-19 pandemic are creating conflicts for couples with young children. Background: National polls suggest that COVID-19 has led to increased conflict for couples in the U.S. Although scholars have not examined the source of these new conflicts, pre-pandemic research suggests that pandemic-related disruptions may create conflicts around paid work and parenting, economic security, politics, and health decision-making. Method: This study uses the Pandemic Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 52 publications
2
50
0
2
Order By: Relevance
“…Future research is necessary to fully understand how unemployment shaped divisions of labor within different‐sex couples during the pandemic and whether findings from Calarco et al. (2020) are supported using nationally representative data.…”
Section: The Pandemic and Gender Inequality: Changes To Work And Familymentioning
confidence: 98%
See 2 more Smart Citations
“…Future research is necessary to fully understand how unemployment shaped divisions of labor within different‐sex couples during the pandemic and whether findings from Calarco et al. (2020) are supported using nationally representative data.…”
Section: The Pandemic and Gender Inequality: Changes To Work And Familymentioning
confidence: 98%
“…In a study of mothers from Southern Indiana, Calarco et al. (2020) found that women with spouses who were between jobs or unemployed perceived a lack of spousal support for their careers. Mothers reported that their spouses, despite not being in paid employment, still relied on them to manage key parenting responsibilities during the pandemic.…”
Section: The Pandemic and Gender Inequality: Changes To Work And Familymentioning
confidence: 99%
See 1 more Smart Citation
“…A survey found higher parenting‐related stress levels among parents who experienced more COVID‐19‐related stressors (Brown et al, 2020). Strain within intimate relationships could also be exacerbated by the presence of children, with parents at potential odds with each other regarding how much exposure poses a risk to children (Calarco et al, 2020). Spillover effects of couple‐level stress are also tied to parenting anxiety and stress during the pandemic (Brown et al, 2020).…”
Section: Families and Health Inequalitiesmentioning
confidence: 99%
“…Whereas some workplaces have shown flexibility in workplace demands, especially for parents of young children, others have not (Williams, 2020). As childcare facilities shut down because of the pandemic, employers who demand that their employees work full time from home expect that childcare duties can be given to—or at least shared with—a partner (Calarco et al, 2020).…”
Section: Families and Health Inequalitiesmentioning
confidence: 99%